PEMBELAJARAN KONTEKSTUAL DENGAN METODE OBSERVASI LINGKUNGAN PADA MATERI ILMU PENGETAHUAN ALAM DAN SOSIAL PERUBAHAN IKLIM - Muhammad Zumamudin; Nabila Ajeng Maharani; Iin Purnamasari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Science learning regarding climate change in elementary schools often falls into abstract theoretical explanations, which reduces students' active engagement and critical thinking skills. This study aims to analyze the effectiveness of implementing environment-based outdoor contextual learning methods in improving the contextual understanding of fifth-grade students at SDN Lamper Kidul 02. The research method used is descriptive qualitative with a reflective case study approach conducted during the teaching assistance phase. Data collection was carried out through participatory observation, interviews, and document analysis of environmental analysis table worksheets filled out by students independently. In learning activities, students were invited outside the classroom to observe physical changes in the school environment and compare them chronologically with past climate conditions. The results showed that the use of outdoor learning methods assisted by analytical worksheets was significantly able to stimulate students' critical thinking skills, trigger logical reasoning regarding the cause-and-effect relationship of environmental damage, and increase student learning enthusiasm through direct interaction with real objects. This study concludes that the contextual outdoor learning method is highly effective as an alternative didactic strategy to transform complex science materials into concrete and meaningful learning experiences for elementary school students.